Letter (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0103-001 4, Aberdare Gardens, Hampstead, LONDON, N.W.6. 1st November, 1937. L.P. Lockhart, Esq., M.D., Messrs. Boots Limited, Station Street, NOTTINGHAM. Dear Lockhart, I am writing to acknowledge the receipt of your letter of the 26th October and the cheque for Two guineas payable to the Honorary Treasurer of the Basque Children's Committee. I am passing the cheque on to him, but you will have seen by the papers last week that the Judicial Committee have decided that the Basque Children should be sent back as soon as practicable. I am so glad that on the Committee I opposed the appointment of such a Legal Commission, on the ground that the Committee should hold the matter in its own hands and take responsibility for a decision made by it on the pure merits of the question. The only other member who opposed the appointment of the Commission was Canon Craven, the representative of His Grace the Archbishop of Westminster, but he opposed it for an entirely different reason: on the grounds that it was meant to be a blocking commission delaying the repatriation of the Children and was an Anti-Catholic move. All the other members of the Committee led themselves into the trap, on a suggestion first made by a lawyer, Mr. Bing, who, I think, is in touch with the Communist Party. Obviously they have greater faith in professional outlooks than I have. You know my personal views on democracy and the professions. Until professional education is radically changed members of most professions will tend to be imbued with an anti-democratic spirit. Of these professions the Legal one is the worst, and legal education is really in an unpardonable condition. but I am running off of my subject. Yours sincerely, 292C/946/2/103